Steel-reinforced concrete structures : assessment and repair of corrosion - El-Reedy, Mohamed A. (Mohamed Abdallah) (CRC Press, 2008)
"Steel-Reinforced Concrete Structures: Assessment and Repair of Corrosion explains the corrosion of reinforced concrete from a practical point of view, highlighting protective design and repair procedures." "The book begins with a discussion of the corrosion phenomena, the effect of concrete properties on corrosion, and the precautions available in the construction stage to mitigate corrosion. It covers the theoretical and practical methods in evaluating the concrete structures and new, practical methods to protect steel reinforcement. The book also includes methods established in the last decade that provide new ways of protecting steel-reinforced bars and the traditional and advanced repairing methods."--Jacket.